Problem Based Learning With The SETS Method To Improve The Student’s Critical Thinking Skill of Senior High School - Devy Alvionita; Prabowo; Z.A. Imam Supardi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study aims to improve students' critical thinking skills through the application of learning materials with the PBL-SETS method. They were developed with the 4D model. This research is pre-experimental used one group pretest and posttest design. Data collection methods used validation, observation, and test. The data analysis technique used is the paired sample T-test. The learning materials have a very valid category and it can be used to improve critical thinking skills. The average critical thinking post-test score is 84 with an N-Gain of 0.7 which categorize as medium, while the overall student completeness reached 87%. The results of data analysis show that t-count = -21,967 and t-table = 1,693 (at df 32 and the significance level of 0.05). Research shows that the use of PBL with the SETS method affects increasing critical thinking skills. The responses of students towards learning by 88% (very good). Based on the results of this study it can be concluded that learning materials of the PBL model with the SETS method can improve the students’ critical thinking skill on fluid dynamic topic. PBL with SETS learning is expected to be able to make students more actively in the process of problem solving directly so that students are easier to develop critical thinking skill. From the indicator of critical thinking skills, students can more easily understand the concept and develop their critical thinking skill.